Pelatihan Pembuatan Eco-Enzyme Sebagai Alternatif Hand Sanitizer pada Masa Pandemi Covid-19 Bagi Masyarakat Desa Mekarsari - Riskaviana Kurniawati; Wiwik Dahani; Edy Jamal Tuheteru; Mustamina Maulani; Fadliah Fadliah; Faldo Matulessy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Covid-19 health protocol regulations cause limited space for people to move, which has an impact on the social and economic life of the community. This condition gives rise to new habits, people must always maintain cleanliness which causes an increasing people's consumption of cleaners such as hand sanitizers, soaps, disinfectants, and others. In addition, people also often consume nutritious foods such as vegetables and fruit, thereby increasing the amount of household waste. However, housing conditions with limited yards and far from Final Disposal Sites (TPA) create a new problem, namely the accumulation of household waste. This condition is also experienced by the people of Mekarsari Village. The technique of converting organic waste into eco-enzymes plays an important role in reducing the amount of organic waste that ends up in landfill. Through community service activities, the team held an Eco-enzyme Making Training as an Alternative Hand Sanitizer during the Covid-19 Pandemic for the people of Mekarsari Village. Community service activities have been carried out and have been able to educate the public in processing household waste, especially organic waste, into eco-enzymes. Furthermore, the eco-enzyme can be used as a hand sanitizer.